Battles to Bridges - Zaharna, R. S. author. aut Link
XVII, 233 p.
Keywords: This book tackles the pressing need to expand the vision of strategic US public diplomacy. It explores the interplay of power politics, culture, identity, and communication and explains how the underlying communication and political dynamics have redefined what 'strategic communication' means in today's international arena.